Transition Metal-Catalyzed Directed C(sp3)–H Functionalization of Saturated Heterocycles - Antermite, Daniele; Bull, James A. (Synthesis, 2019)
Synthetic methods that can readily access saturated heterocycles with different substitution patterns and with control of stereo- and regiochemistry are of huge potential value in the development of new medicinal compounds. Directed C–H functionalization of simple and commercially available precursors offers the potential to prepare diverse collections of such valuable compounds that can probe the different available exit vectors from a ring system. Nonetheless, the presence of the Lewis basic heteroatoms makes this a significant challenge. This review covers recent advances in the catalytic C–H functionalization of saturated heterocycles, with a view to different heterocycles (N, O, S), substitution patterns and transformations.1 Introduction2 α-C–H Functionalization with Directing Group on Nitrogen3 C–H Functionalization at Unactivated C(3), C(4), and C(5) Positions3.1 C–H Functionalization at C(3) with Directing Groups at C(2)3.2 C–H Functionalization at C(3), C(4), and C(5): Directing Groups at C(4) and C(3)4 Transannular C–H Functionalization5 Conclusion
Keywords: C–H functionalization; saturated heterocycles; transition metal catalysis; stereoselectivity; regioselectivity